A non-invasive, 3D, dynamic MRI method for measuring muscle moment arms in vivo: Demonstration in the human ankle joint and Achilles tendon. Issue 1 (January 2015) - Clarke, E.C.; Martin, J.H.; d'Entremont, A.G.; Pandy, M.G.; Wilson, D.R.; Herbert, R.D.
Highlights A 3D, dynamic MRI method for measuring muscle moment arms in vivo is presented. The method can be applied to a single joint rotation cycle. The method is validated using a custom apparatus. The method is demonstrated in the Achilles tendon of 10 healthy subjects.